2019
DOI: 10.1111/anu.12907
|View full text |Cite
|
Sign up to set email alerts
|

Dietary taurine supplementation to a plant protein source‐based diet improved the growth and intestinal immune function of young grass carp (Ctenopharyngodon idella)

Abstract: The effects of taurine supplementation on the growth and intestinal immune function in young grass carp (Ctenopharyngodon idella) were investigated in this study. A total of 540 fish (initial average weights of 255.74 ± 0.65 g) were fed one fishmeal diet and five all‐plant protein source‐based diets with graded levels of taurine (0 to 1.98g/kg diet) for 60 days, and then challenged with Aeromonas hydrophila for 14 days. First, the results showed that the taurine supplementation improved growth (PWG, TGC, FI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 87 publications
(142 reference statements)
1
19
1
Order By: Relevance
“…In our study, fish fed with low level replacement of rapeseed meal diet phosphorylated Grb10, indicated that diet with low level of rapeseed meal could activate Grb10, and inhibit mTOR pathway, that enhanced lipolysis and thermogenesis of Chinese perch. Similar results were found in grass carp [44] and juvenile white shrimp [45], the results are in line with other studies.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, fish fed with low level replacement of rapeseed meal diet phosphorylated Grb10, indicated that diet with low level of rapeseed meal could activate Grb10, and inhibit mTOR pathway, that enhanced lipolysis and thermogenesis of Chinese perch. Similar results were found in grass carp [44] and juvenile white shrimp [45], the results are in line with other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Plant protein intake is also correlated to impaired digestion and increased oxidative stress in aquatic animals (Gu et al., 2017; Tibaldi et al., 2006; Yamamoto et al., 2008). The digestive capacity of fish depends on the functional intestine (Yan et al., 2019), which is usually affected by the enteritis (Chen et al., 2015; Zhang et al., 2017). It has been reported that dietary plant protein intake in fish is related to intestinal inflammation reflected by decreased levels of anti‐inflammatory cytokines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The primary antibodies for TOR and phosphorylation of TOR Ser 2448 are the same as described by Yan et al. (2019). Subsequently, the membranes were washed and reacted with goat anti‐rabbit horseradish peroxidase‐conjugated secondary antibody (Santa Cruz Biotechnology) for 2 hr.…”
Section: Methodsmentioning
confidence: 99%
“…After that, membranes reacted with primary antibodies (4°C, 12 hr). The primary antibodies for TOR and phosphorylation of TOR Ser 2448 are the same as described byYan et al (2019). Subsequently,…”
mentioning
confidence: 99%